Mathematics
         
语言:中文    Language:English
On line Solution of Monovariate Equation:
    Input any unary equation directly, and then click the "Next" button to obtain the solution of the equation.
    It supports equations that contain mathematical functions.
    Current location:Equations > Monovariate Equation > The history of univariate equation calculation > Answer

    Overview: 1 questions will be solved this time.Among them
           ☆1 equations

[ 1/1 Equation]
    Work: Find the solution of equation (x-3)(x+2)(x+1)-24-5x+46 = 0 .
    Question type: Equation
    Solution:Original question:
     ( x 3)( x + 2)( x + 1)245 x + 46 = 0
     Left side of the equation = ( x 3)( x + 2)( x + 1) + 225 x
    The equation is transformed into :
     ( x 3)( x + 2)( x + 1) + 225 x = 0
    Remove the bracket on the left of the equation:
     Left side of the equation = x ( x + 2)( x + 1)3( x + 2)( x + 1) + 225 x
                                             = x x ( x + 1) + x × 2( x + 1)3( x + 2)( x + 1) + 225 x
                                             = x x x + x x × 1 + x × 2( x + 1)3( x + 2)( x + 1)
                                             = x x x + x x × 1 + x × 2 x + x × 2 × 1
                                             = x x x + x x × 1 + x × 2 x + x × 23
                                             = x x x + x x × 1 + x × 2 x 3 x 3
                                             = x x x + x x × 1 + x × 2 x 3 x 3
                                             = x x x + x x × 1 + x × 2 x 3 x 3
                                             = x x x + x x × 1 + x × 2 x 3 x 3
                                             = x x x + x x × 1 + x × 2 x 3 x 3
                                             = x x x + x x × 1 + x × 2 x 6 x 3
                                             = x x x + x x × 1 + x × 2 x 6 x 3
                                             = x x x + x x × 1 + x × 2 x 6 x 3
                                             = x x x + x x × 1 + x × 2 x 12 x 3
    The equation is transformed into :
      x x x + x x × 1 + x × 2 x 12 x 3 = 0

    After the equation is converted into a general formula, it is converted into:
    ( x + 4 )( x - 2 )( x - 2 )=0
    From
        x + 4 = 0
        x - 2 = 0
        x - 2 = 0

    it is concluded that::
        x1=-4
        x2=2
        x3=2
    
    There are 3 solution(s).


解程的详细方法请参阅:《方程的解法》



Your problem has not been solved here? Please go to the Hot Problems section!





  New addition:Lenders ToolBox module(Specific location:Math OP > Lenders ToolBox ),welcome。